Emerging Local Securities and Derivatives Markets : Recent Developments and Policy Issues - Ramaswamy, Ramana; Ilyina, Anna.; Mathieson, Donald; Roldos, Jorge (Washington, D.C. : International Monetary Fund, 2004)
In response to the volatility of capital flows since the mid-1990s, many emerging market economies have taken a variety of steps designed to 'selfinsure' against volatile capital flows. One such measure has been the development of local securities and derivatives markets as an alternative source of funding the public and corporate sectors. This paper examines this self-insurance policy, focusing on the extent to which emerging markets have developed local securities and derivatives, and what key policy issues have arisen as a result.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet